Effects of neuroserpin on clinical outcomes and inflammatory markers in Chinese patients with acute ischemic stroke. (3rd October 2017) - Wu, Weiwen; Asakawa, Tetsuya; Yang, Qianghong; Zhao, Jun; Lu, Lixia; Luo, Yunhe; Gong, Ping; Han, Sha; Li, Wei; Namba, Hiroki; Wang, Liang
Abstract: Objective: Neuroserpin (NSP) is known for its neuroprotective effects. The aim of this study was to investigate the relationship between NSP level and clinical outcomes and inflammatory markers in Chinese patients with acute ischemic stroke. Methods: A total of 133 patients with acute cerebral infarction (ischemia group) and 44 controls were recruited. The modified Rankin Scale (mRS) was used to determine the functional outcome three months after onset. We investigated the relationship between serum NSP levels [on admission and a decrease in NSP levels (10 days after admission versus on admission)] and serum levels of several inflammatory markers. Results: We confirmed that NSP levels on admission in the ischemia group were significantly higher than those in the control group. NSP levels in patients with good outcomes were significantly higher than those in patients with poor outcomes. NSP levels on admission were associated with having a good outcome in these patients. We found that a larger decrease in NSP levels (on admission vs. 10 days after admission) was correlated with lower serum levels of IL-6, IL-1β, and ICAM-1 10 days after admission. Conclusions: A larger decrease in NSP levels related to lower levels of inflammatory marker, while higher NSP levels were associated with lower inflammatory markers and better functional outcomes. Decreasing the infarct size may play a role in this process. These results provide more evidence of the neuroprotective effect of NSP in cerebral ischemic patients. Decrease in the Serum NSP level and NSP level at admission may be considered as potential predictive factors for outcome of acute ischemic stroke.